Continuous glucose monitoring‐based time‐in‐range using insulin glargine 300 units/ml versus insulin degludec 100 units/ml in type 1 diabetes: The head‐to‐head randomized controlled InRange trial. Issue 2 (14th November 2022) - Battelino, Tadej; Danne, Thomas; Edelman, Steve V.; Choudhary, Pratik; Renard, Eric; Westerbacka, Jukka; Mukherjee, Bhaswati; Pilorget, Valerie; Coudert, Mathieu; Bergenstal, Richard M.
Abstract: Aim: To use continuous glucose monitoring (CGM)‐based time‐in‐range (TIR) as a primary efficacy endpoint to compare the second‐generation basal insulin (BI) analogues insulin glargine 300 U/ml (Gla‐300) and insulin degludec 100 U/ml (IDeg‐100) in adults with type 1 diabetes (T1D). Materials and Methods: InRange was a 12‐week, multicentre, randomized, active‐controlled, parallel‐group, open‐label study comparing glucose TIR and variability between Gla‐300 and IDeg‐100 using blinded 20‐day CGM profiles. The inclusion criteria consisted of adults with T1D treated with multiple daily injections, using BI once daily and rapid‐acting insulin analogues for at least 1 year, with an HbA1c of 7% or higher and of 10% or less at screening. Results: Overall, 343 participants were randomized: 172 received Gla‐300 and 171 IDeg‐100. Non‐inferiority (10% relative margin) of Gla‐300 versus IDeg‐100 was shown for the primary endpoint (percentage TIR ≥ 70 to ≤ 180 mg/dl): least squares (LS) mean (95% confidence interval) 52.74% (51.06%, 54.42%) for Gla‐300 and 55.09% (53.34%, 56.84%) for IDeg‐100; LS mean difference (non‐inferiority): 3.16% (0.88%, 5.44%) (non‐inferiority P = .0067). Non‐inferiority was shown on glucose total coefficient of variation (main secondary endpoint): LS mean 39.91% (39.20%, 40.61%) and 41.22% (40.49%, 41.95%), respectively; LS mean difference (non‐inferiority) −5.44% (−6.50%, −4.38%) (non‐inferiority P  < .0001). Superiority of Gla‐300 over IDeg‐100 was not shown on TIR. Occurrences of self‐measured and CGM‐derived hypoglycaemia were comparable between treatment groups. Safety profiles were consistent with known profiles, with no unexpected findings. Conclusions: Using clinically relevant CGM metrics, InRange shows that Gla‐300 is non‐inferior to IDeg‐100 in people with T1D, with comparable hypoglycaemia and safety profiles.